Pengaruh Citra Merek, Inovasi Produk dan Iklan Terhadap Keunggulan Bersaing Produk Eskrim Wall’s Di Tambun Selatan, Kabupaten Bekasi - Edy Supriyantony; Aditya Jayadi (LPPM STIE Bisnis Internasional Indonesia, 2021)
The high intensity of competition in the ice cream product industry requires businesses to have a competitive advantage that differentiates them from their competitors. Competitive advantage can be obtained through brand image building, product innovation and advertising. This study aims to determine the effect of brand image, product innovation and advertising, (partially or simultaneously) on the competitive advantage of Walls ice cream products. The research sample amounted to 160 people who were determined based on the formula